Investigation of shape memory characteristics and production of HfZrTiFeMnSi high entropy alloy by mechanical alloying method - Guler, Omer; Simsek, Tuncay; Ozkul, Iskender; Avar, Baris; Canbay, Canan A.; Chattopadhyay, Arun K.; Guler, Seval H. (Elsevier, 2022)
High entropy alloy (HEA) with shape memory effect (SME) has been the subject of great interest for the past few decades. However, with the increased demands for new materials for high thermal applications, the research activities on the multi elemental high entropy shape memory alloys (HESMA) have been increased by many folds recently. The nano crystalline HEA powder with shape memory effect developed in this study, HfZrTiFeMnSi, was produced by mechanical alloying (MA) for the first time. In this method equiatomic ratio of Hf, Zr, Ti, Fe, Mn, and Si were mixed together and milled by MA process for 100 h. The powder formed was of amorphous in nature. Elemental mapping of the powder from SEM-EDS revealed homogeneity of the alloying elements confirming successful fabrication of HfZrTiFeMnSi HEA powder. The DSC studies from ambient to 500 degrees C of the annealed alloy powders showed reversible austenitic to martensitic (A <-> M) transformations. The A <-> M transformation hysteresis seemed to vary with the milling time and annealing temperature. The enthalpy values, Delta H, for the transformation were calculated from the DSC plots using tangent method for peak area calculation. Regardless of the annealing temperature, the thermal analysis revealed that the Delta H, equilibrium temperature (T0), and crystallization temperature values decreased with the increasing milling time.
Keywords: High entropy alloys (HEAs); Shape Memory Alloys (SMA); Mechanical Alloying; Differential scanning calorimetry (DSC)